Perancangan Alat Pengepresan Baglog Jamur Tiram yang Ergonomis Guna Mengurangi Risiko Cidera Otot dan Meningkatkan Produktivitas Kerja: Studi Kasus : Home Industry Jamur Tiram - Mela, Arij Basmin Basmala; Putu Eka Dewi Karunia Wati (Fakultas Teknik UMRI, 2024)
This research discusses the design of an ergonomic oyster mushroom baglog pressing tool which aims to increase work productivity in Pak Heru's home oyster mushroom industry and reduce the risk of muscle injury. Workers' muscle injuries can occur during the baglog pressing process which is carried out manually in a bent sitting position. It is hoped that the ergonomic design of this tool will speed up baglog pressing time and increase production efficiency. To determine the risk of muscle injury, the study used Nordic Body Map (NBM) and Rapid Entire Body Assessment (REBA) measurements. And the House of Quality (HOQ) method is also used to determine customer needs and create new products. The trial results of designing an ergonomic oyster mushroom baglog peeler showed that work productivity increased. The research results show that baglog pressing machines can increase productivity significantly compared to previous processes carried out manually. After use of the designed device, there is a low level of risk of muscle injury, according to analyzes using NBM and REBA. Apart from that, the costs for making baglog and oyster mushroom pressing equipment have also been calculated. With a production output of 60 baglogs per hour and 420 baglogs per day, the ergonomic baglog pressing machine increases work productivity and reduces the risk of muscle injury.